Cigarette smoke modifies and inactivates SPLUNC1, leading to airway dehydration. Issue 12 (11th June 2018) - Moore, Patrick J.; Reidel, Boris; Ghosh, Arunava; Sesma, Juliana; Kesimer, Mehmet; Tarran, Robert
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is a growing cause of morbidity and mortality worldwide. Cigarette smoke (CS) exposure, a major cause of COPD, dysregulates airway epithelial ion transport and diminishes airway surface liquid (ASL) volume. Short palate lung and nasal epithelial clone 1 (SPLUNC1) is secreted into the airway lumen where it maintains airway hydration via interactions with the epithelial Na + channel (ENaC). Although ASL hydration is dysregulated in CS‐exposed/COPD airways, effects of CS on SPLUNC1 have not been elucidated. We hypothesized that CS alters SPLUNC1 activity, therefore contributing to ASL dehydration. CS exposure caused irreversible SPLUNC1 aggregation and prevented SPLUNC1 from internalizing ENaC and maintaining ASL hydration. Proteomic analysis revealed αβ‐unsaturated aldehyde modifications to SPLUNCL's cysteine residues. Removal of these cysteines prevented SPLUNC1 from regulating ENaC/ASL volume. In contrast, SPX‐101, a peptide mimetic of natural SPLUNC1, that internalizes ENaC, but does not contain cysteines was unaffected by CS. SPX‐101 increased ASL hydration and attenuated ENaC activity in airway cultures after CS exposure and prolonged survival in a chronic airway disease model. These findings suggest that the CS‐induced defects in SPLUNC1 can be circumvented, thus making SPX‐101 a novel candidate for the treatment of mucus dehydration in COPD.—Moore, P. J., Reidel, B., Ghosh, A., Sesma, J., Kesimer, M., Tarran, R. Cigarette smoke modifies and inactivates SPLUNC1, leading to airway dehydration. FASEB J. 32, 6559–6574 (2018). www.fasebj.org